A forecast of international migration flows into EU countries until 2050 - Polovyi, Mykola (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2018)
The subject of this paper is international migration into EU countries. The research objective is a quantitative estimation of the volume of international migration flows into European countries and their close neighbors until 2050. The forecast of international migration flows is based on the author’s own model of global international migration. The model is based on a synergetic approach and assumptions that the level of migration is determined first of all by the number of existing migrants from that country. The data used for the forecast is UN data on migration flows in 1990-2015, and the UN’s predictions regarding changes in population between now and 2050. The forecast is based on the medium scenario of demographic development offered by the UN. Countries with a current population of more than 5 million are taken into consideration as potential sources of immigration. The predicted values of the total number of international migration flows to each of the EU and neighboring countries for each five-year period until 2050 are determined. The predicted migration flows from EU countries are also determined. It is concluded that the forecasts allow us to claim that the problem of migration will continue for EU countries. However, the essence of this problem is not the prevention of excess migration, but attracting migrants to the countries of the ‘second Europe.’

Tematyka prezentowanego artykułu dotyczy problematyki międzynarodowej migracji do państw członkowskich Unii Europejskiej. Celem badawczym artykułu jest ilościowe oszacowanie wielkości międzynarodowych przepływów migracyjnych do państw europejskich i ich bliskich sąsiadów do 2050 r. Autor posłużył się autorskim modelem migracji w skali globalnej. Opiera się on na synergicznym podejściu i założeniach, że poziom migracji określa przede wszystkim liczba istniejących imigrantów z tego państwa. W artykule wykorzystano dane ONZ dotyczące przepływów migracyjnych w latach 1990-2015. Umożliwiło to oszacowanie prognozy dotyczących m.in. zmian w populacji między rokiem 2050 a stanem obecnym. Prognoza ta opiera się na średnim scenariuszu rozwoju demograficznego ONZ. Jako potencjalne źródła imigracji autor wziął pod uwagę współczesne państwa o populacji powyżej 5 milionów. W przedłożonym tekście ujęto przewidywania dotyczące wartości całkowitej liczby przepływów międzynarodowych do każdego z państw UE i państw sąsiednich na każdy pięcioletni okres do roku 2050 oraz przepływy migracyjne z państw UE. Stwierdzono, że prognozy pozwalają nam twierdzić, że problem migracji będzie cały czas dotyczył państw UE. Jednak istotą tego problemu nie jest zapobieganie nadmiernej migracji, ale przyciąganie migrantów do krajów „drugiej Europy”.
Prognoza przepływów międzynarodowych migracji do państw UE do 2050
Keywords: forecasts of international migration flows until 2050; simulation of international migration; migration to the EU; prognozy międzynarodowych przepływów migracyjnych do 2050 r; Symulacja migracji międzynarodowej; migracja do UE